Effect of Concurrent Strength and Plyometric Training on Selected Biomotor Abilities - W. Vinu2, R. Muthu Eleckuvan3, K. Jothi1* (Recent Research in Science and Technology, 2010)
The underlying principle of this study was to assess the effect of eight weeks concurrent strength and plyometric training in enhancing the selected biomotor abilities. For the purpose of this study, thirty male volleyball specialization students from the department of physical education and sports sciences, Annamalai university, aged 20 to 22 years took part in the study. Subjects were randomly assigned to either concurrent training (n=15) or control (n=15) group. The training regimen lasted for eight weeks. The selected criterion variables were assessed using standard tests and procedures, prior to and immediately after the training programme. Analysis of covariance was employed to establish the degree of significant modification on chosen criterion variables. The findings of the study revealed that eight weeks of concurrent training had an effectiveness of 4.13% on leg strength, 11.81% on strength endurance, 0.40% on speed, and 7.53% on anaerobic power. These findings suggest that the concurrent strength and plyometric training programme have statistically significant influence in developing the selected criterion variables.